Mangerial Competence of the Head of Madrasah in Managing and Developing Islamic Education (PAI) at Madrasah Aliyah Pesantren Hidayatul Maarifiyah, Riau Province - Maisah Maisah; Sudur Sudur; Fadlilah Fadlilah; Husin Husin (Universitas Muhammadiyah Enrekang, 2024)
Education plays a pivotal role in shaping the character, intelligence, and skills of the nation’s youth, aligning with the goals of Indonesia's National Education System. This study explores the managerial competence of the head of Madrasah Aliyah Pondok Pesantren Hidayatul Ma’arifiyah in Pelalawan Regency, focusing on the planning, organizing, implementation, and control of Islamic Education (PAI). Using a qualitative descriptive approach, data were collected through interviews, observation, and documentation. Results reveal the headmaster’s critical role in enhancing PAI through effective resource management, discipline enforcement, and stakeholder engagement. Challenges include adapting to pesantren-specific needs and societal demands while integrating modern pedagogical methods. The study highlights strategies for improving teacher professionalism through training, infrastructure upgrades, and a curriculum aligned with workforce demands. The headmaster’s leadership fosters a balance of formal and non-formal education, creating a conducive learning environment. This research emphasizes the importance of managerial competence in achieving the madrasah’s vision of producing ethical, competent, and innovative graduates.